Tracing Educational Concepts in the Qur’an: A Semantic Meaning Approach to Holistic Learning - Kamridah, Kamridah; Husnaeni , Maftuha; Deliany, Susy (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2025)
In an era shaped by fragmented educational ideals and ethical uncertainty, the pursuit of integrative learning models has become increasingly critical. Although the Qur'an is widely regarded as a source of moral and intellectual guidance, its semantic construction of educational concepts remains largely unexplored within contemporary holistic education discourse. This study addresses that gap by applying Izutsu’s semantic analysis to examine how the Qur’an presents a comprehensive vision of education that integrates intellectual, spiritual, moral, and social dimensions. Employing a case study approach within an interpretive paradigm, the research systematically identifies and analyzes six key educational terms drawn from the Qur'anic text. These terms are tarbiyah (nurturing growth), ta’lim (teaching and imparting knowledge), ta’aruf (mutual recognition and understanding), tazkiyah (purification and self-enhancement), ta’dib (discipline and character refinement), and ta’alluq (connection and meaningful attachment). Through meticulous semantic tracing and cross-validation with classical exegetical sources, the study reveals how these terms form an interconnected conceptual network reflecting the Qur’an's holistic perspective on human development. The findings suggest that this educational framework emerged as a response to pre-Islamic social inequalities, the limited accessibility of knowledge, and the need for education to drive personal and societal transformation. By integrating Islamic educational philosophy with humanistic and posthumanistic theories, the study contributes a culturally grounded yet globally relevant model of education. Its implications extend to curriculum design, teacher preparation, and policy reform, affirming the Qur’anic vision of education as a transformative process that cultivates ethical, inclusive, and ecologically conscious individuals equipped for the complexities of modern life.